(untitled) (IUBAT Review, 2024)
This study investigated language attitudes of the first generation of the Urdu-speaking Bihari Community in Dhaka city. In this paper, the term ‘first generation’ refers to persons who immigrated to erstwhile East Pakistan (now Bangladesh) during the partition in 1947 and were born before the liberation warof 1971.Language attitudeis defined in this research as an individual or communal expression toward Urdu and Bangla, as well as language choices and use by the first generation. The purpose of this research was to investigate language attitudes of the first generation towards their mother tongue, Urdu, and the language of the dominant community, Bangla, in a bilingual situation in the Bihari community of Dhaka, and the present condition of Urdu in Bangladesh. The primary goal was to determine if they were positive, negative, or neutral to their own language, Urdu and to the dominant Bengali language. This study adopted a mixed-methods approach, and the data were obtained through a questionnaire and interviews with some respondents of the Bihari community of Geneva camp, Dhaka. The findings highlight the impact of their language attitudes on their language use and choice in bilingual situations and reveal that the first generation has a more positive attitude toward Urdu than Bangla. This study may serve as a specimen for future academics to assess how the language of a community shifts and how language attitudes of that particular community change over time. IUBAT Review—A Multidisciplinary Academic Journal, 7(1): 01-25